Alarming Rates of Obesity and Diabetes in Urban Africa: A Case Study in Bamako, Mali. (29th May 2020) - Kameli, Yves; Meunier, Joseph; BESANCON, Stephane; Savy, Mathilde; Martin-Prevel, Yves
Abstract: Objectives: Sahelian cities are growing very fast with changes in lifestyles and rise in obesity and associated chronic diseases. Reliable data on the nutritional situation in African cities is dreadfully missing. The aim of this study was to estimate overweight and obesity rates and the risk of pre-diabetes and diabetes in Bamako in order to trigger appropriate prevention measures. Methods: From November 2019 to January 2020, a cross-sectional survey was conducted among a representative sample of 2040 households in Bamako, Mali. In each household, a random selection of individuals was stratified on age groups: 12–17 y, 18–29 y, 30–49 y, ≥50 y. Anthropometric measurements (weight, height, waist circumference) and plasma fasting glycemia (PFG) using Hemocue® devices were performed according to international procedures. The prevalence of overweight and obesity were defined by Body Mass Index (BMI) values using WHO cut-points for adults (25 kg/m2 ≤ BMI < 30 kg/m2 and BMI ≥ 30 kg/m2, respectively) and International Obesity Task Force cut-points for adolescents (IOTF-25 and IOTF-30, respectively). Abdominal obesity was defined by a waist circumference ≥88 cm for women and ≥102 cm for men. Risks of pre-diabetes and diabetes were defined by a PFG between 100 and 125 mg/dl and ≥126 mg/dl, respectively. Results: All ages combined, the prevalence of overweight was 19.5% among men (n = 1933) and 24.4% among women (n = 2724) ( P  < 0.0001). The prevalence of obesity was 6.2% among men and 21.0% among women ( P  < 0.0001). We also found that 29.9% of women presented abdominal obesity vs 5.7% in men ( P  < 0.0001). Women older than 30 y (n = 1395) were the most affected, however women aged 12–17 y (n = 670) and 18–29 y (n = 881) presented alarming figures too (11.5% and 21.2% of them were overweight, respectively). Globally, 13.3% of individuals were at risk of pre-diabetes and 2.5% at risk of diabetes, with no significant gender differences. The risk of pre-diabetes ranged from 10.2% in the 12–17 y age-group to 17.8% in the ≥50 y age-group. Conclusions: Our data calls for urgent actions to tackle the burden of overweight and obesity, especially among women, and to minimize the risk of diabetes and other associated non-communicable diseases in Bamako. Funding Sources: French Embassy of Mali, French Institute of Research for sustainable Development (IRD).